(3OhQ eQGcR GdCHMGK hJCKjQgG Ydi UfY GdSjGSI GdNGQLjI GdCeQjcjI (B: s (3OQGSI MGdI dCge eQGcR GdCHMGK ai GdhdGjGJ GdeJMOI GdBeQjcjI ai GdaJQI(B1996\2005 / s - (3eQhI eMeO YHOGdYRjR eUWais; (3MSf fGaYI (B: s ((3GdbGgQI (B: s (3eQhI eMeO YHOGdYRjR eUWai (B: s, 2009)
(3JJHY CgejI GdOQGSI ef GdOhQ Gdege GdPi JdYHg eQGcR GdCHMGK ai GdhdGjGJ GdeJMOI ai YedjI UfY GdSjGSI GdNGQLjI HUaJgG hGMOI ef Cge GdeDSSGJ ZjQ GdQSejI hcPdc dchfgG XGgQI CeQjcjI aQjOI ef fhYgG hdbO GROGO OhQ gPg GdeQGcR ai GdSGMI GdSjGSjI GdCeQjcjI ai CYbGH GdMGOi YTQ ef SHJeHQ NGUI eY eLF LhQL HhT Edi GdMce hJYjjf GdYOjO ef CbWGH JjGQ GdeMGaXjf GdLOO ai efGUH gGeI ai EOGQJg hge jfJehf ai eYXege Edi eQGcR GdCHMGK GdeMGaXI eKd (B: (3CeQjcGf EfJQHQGjR (B- (3gjQjJL (B- (3eTQhY GdbQf GdCeQjci GdLOjO hdbO CUOQhG GdYOjO ef GdOQGSGJ hGdcJGHGJ GdJi COJ Edi HdhQI SjGSI EOGQI HhT JLGg GdeGdejf GdYQHi hGdESdGeis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdGbJUGO hGdYdhe GdSjGSjI (B- (3bSe GdYdhe GdSjGSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdSjGSI GdNGQLjI GdCeQjcjI s; (3UfY GdSjGSI GdNGQLjI s; (3eQGcR GdCHMGKs